Pengajaran Bahasa Inggris bagi Siswa SD Persiapan Menuju Desa Aan sebagai Smart Village - Ni Wayan Mekarini; Ni Nyoman Ardani; I Putu Raditya; I Made Agung Rai Antara; Komang Shintya Nita Kristina Putri; I Made Sunata; Putu Asda Ryawan (Pubfine Media Group, 2024)
The Thematic Social Services is one of students' sercices to the community to implement the Tri Darma of Higher Education by doing certain contributions to society. Triatma Mulya University held social services program in some villages in Bali and one of them done in Aan Village, Banjarangkan District, Klungkung Regency, Bali for 5 weeks from 08 January 2024 to 06 February 2024 with the theme